Seasonal variation of serum KL-6 and SP-D levels in bird-related hypersensitivity pneumonitis - Okamoto, Tsukasa; Tsutsui, Toshiharu; Suhara, Kozo; Furusawa, Haruhiko; Miyazaki, Yasunari; Inase, Naohiko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
N/A